Molecular characterisation of Cryptosporidium spp. in lambs in the south central region of the State of São Paulo - Zucatto, A. S. [UNESP]; Aquino, M. C. C. [UNESP]; Inácio, S. V. [UNESP]; Figueiredo, R. N. [UNESP]; Pierucci, J. C. [UNESP]; Perri, S. H. V. [UNESP]; Meireles, M. V. [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
Considering the proximity of sheep farmers to animals that are possibly diseased or releasing fecal oocysts into the environment and the marked pathogenicity in lambs, the aim of this study was to determine the occurrence and to molecularly characterize the infection by Cryptosporidium spp. in lambs in the South Central region of the state of São Paulo, Brazil. A total of 193 fecal samples were collected from sheep of several breeds, males and females, aged up to one year. Polymerase chain reaction (nested-PCR) was used to amplify DNA fragments from the subunit 18S rRNA gene and indicated 15% positivity; sequencing of amplified fragments was possible for 19 samples. Analysis of the obtained sequences showed that the identified species were Cryptosporidium xiaoi for 15 samples, constituting thus the first molecular characterization study of this Cryptosporidium species in Brazil. Cryptosporidium ubiquitum was identified for three samples and Cryptosporidium meleagridis for one sample; the latter two are considered zoonotic species.

Devido à proximidade de criadores de ovinos com animais possivelmente doentes e/ou eliminando oocistos fecais no ambiente e pela acentuada patogenicidade em cordeiros o objetivo foi, determinar a ocorrência e caracterizar molecularmente a infecção por Cryptosporidium spp. em cordeiros na região Centro Sul do Estado de São Paulo, Brasil. Num total de 193 amostras de fezes foram coletadas de ovinos de diversas raças, machos e fêmeas, com idade de até um ano. Por meio da reação em cadeia da polimerase (nested PCR) para a amplificação de fragmentos de DNA a partir do gene da subunidade 18S do rRNA houve positividade de 15% e o sequenciamento dos fragmentos amplificados foi possível em 19 amostras. A análise das sequências obtidas mostraram que as espécies identificadas nesses animais foram Cryptosporidium xiaoi em 15 amostras, sendo o primeiro estudo de caracterização molecular desta espécie de Cryptosporidium no Brasil. Cryptosporidium ubiquitum em três amostras, e Cryptosporidium meleagridis em uma amostra, sendo estas duas últimas consideradas espécies zoonóticas.
Caracterização molecular de Cryptosporidium spp. em cordeiros na região centro sul do Estado de São Paulo
Keywords: Cryptosporidiosis; Sheep; Nested-PCR; Genotype; Cryptosporidiose; Ovinos; |Nested-PCR; Genótipo